2023
DOI: 10.1038/s42255-023-00891-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular control of endurance training adaptation in male mouse skeletal muscle

Regula Furrer,
Barbara Heim,
Svenia Schmid
et al.

Abstract: Skeletal muscle has an enormous plastic potential to adapt to various external and internal perturbations. Although morphological changes in endurance-trained muscles are well described, the molecular underpinnings of training adaptation are poorly understood. We therefore aimed to elucidate the molecular signature of muscles of trained male mice and unravel the training status-dependent responses to an acute bout of exercise. Our results reveal that, even though at baseline an unexpectedly low number of genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
9
19
0
Order By: Relevance
“…We performed transcriptomic analysis of the gastrocnemius muscle of the control and exercise trained mice, with and without BMAL1. Analysis of the muscle from vehicle control and trained mice identified 142 DEGs after training which is consistent with prior studies [3,36]. Within those DEGs, 67 were upregulated, and 75 were downregulated after training, Figure 3A.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…We performed transcriptomic analysis of the gastrocnemius muscle of the control and exercise trained mice, with and without BMAL1. Analysis of the muscle from vehicle control and trained mice identified 142 DEGs after training which is consistent with prior studies [3,36]. Within those DEGs, 67 were upregulated, and 75 were downregulated after training, Figure 3A.…”
Section: Resultssupporting
confidence: 89%
“…These outcomes suggest that the well-defined molecular responses to exercise training in skeletal muscle requires BMAL1 and/or a functional circadian clock mechanism, but in its absence requires a far larger network of genes to elicit adaptations. Our findings have similarities to recent work demonstrating the contribution of muscle specific Ppargc1a to the exercise training response [36]. This is not surprising as it has been shown that Ppargc1a is a clock output gene in skeletal muscle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…PGC-1α plays a crucial role in determining muscle fiber type. 42 Mitochondria regulate energy generation, metabolic activities, and cellular signaling and are of paramount importance in maintaining overall cellular health. Considering this, mitochondrial impairment becomes a precipitating factor in the onset of various diseases including hepatic disorders, diabetes mellitus, and dementia.…”
Section: ■ Discussionmentioning
confidence: 99%
“…PGC-1α plays a crucial role in determining muscle fiber type . Mitochondria regulate energy generation, metabolic activities, and cellular signaling and are of paramount importance in maintaining overall cellular health.…”
Section: Discussionmentioning
confidence: 99%